Assessing the Value of Subscription Journal Packages and Open Access Journal Articles in a Community College Context - Duncan Claflin; Tim Dolan (Journal of Librarianship and Scholarly Communication, 2023)
Introduction: Academic libraries are facing two trends: the rising cost of journal subscriptions—the ongoing ‘serials crisis’—and the increasing availability of scholarly journal articles through free, open access channels. Methods: This study analyzed the bibliographies from 116 research projects created by students across disciplines at a small community college, and classified citations to journal articles based on the simplest way students could have accessed them. Results: more than 60% of the scholarly journal articles that students used are available to them for free, while an additional 18% are available through state-sponsored database subscriptions available to any Massachusetts resident. Only 17% of the journal articles used were available to students solely through the library’s database packages, and more than half of those articles were used by students in the ADN nursing program. Discussion: These findings call into question the value of expensive subscription databases to community college libraries and suggest a pattern of diminishing return on investment and value. The trend towards cancellation of ‘big deal’ journal packages at large institutions addresses similar concerns, though the dynamics are somewhat different at small institutions. Conclusion: The paper concludes by suggesting some steps that small academic libraries might take to adapt to this changing publishing environment, in the areas of collection development and information literacy instruction, in order to better serve students.